Material Encounters between Jews and Christians: From the Silk and Spice Routes to the Highlands of Ethiopia - Arfeen-Wegner, Percy; Cuffel, Alexandra; Cuffel, Alexandra; Dege-Müller, Sophia; Eliyahu, Meydad; Eliyahu, Yehoshua; Gajda, Iwona; Gamliel, Ophira; Hunt, Lucy-Anne; João Ramos, Manuel; Kribus, Bar; Kribus, Bar; et al. (Jewish Engagements, 2024)
This book demonstrates the potential of material culture, including artworks and archaeological finds, to shed new light on Jewish-Christian interaction in medieval and early modern times. Previous studies have focused on areas where Jews lived as a minority under Christian rule, such as in Western Europe and the Byzantine Empire. This book, on the other hand, explores the eastern Mediterranean to Central Asia, the Red Sea and India, where Jews and Christians interacted on a different footing